2020
DOI: 10.3389/fmicb.2020.588952
|View full text |Cite
|
Sign up to set email alerts
|

Immunization With Outer Membrane Vesicles Derived From Major Outer Membrane Protein-Deficient Salmonella Typhimurium Mutants for Cross Protection Against Salmonella Enteritidis and Avian Pathogenic Escherichia coli O78 Infection in Chickens

Abstract: Colibacillosis is an economically important infectious disease in poultry, caused by avian pathogenic Escherichia coli (APEC). Salmonella enterica serovar Enteritidis (S. Enteritidis) is a major cause of food-borne diseases in human circulated through poultry-derived products, including meat and chicken eggs. Vaccine control is the mainstream approach for combating these infections, but it is difficult to create a vaccine for the broad-spectrum protection of poultry due to multiple serotypes of these pathogens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 57 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…Typhimurium UK-1 [ 12 ] QS0071 S . Typhimurium UK-1 ∆ rfbP ∆ fliC ∆ fljB ∆ ompA [ 8 ] QS0072 Δ rfbP Δ fliC Δ fljB Δ ompA with plasmid pHbp+UreB-VacA-CagA This study QS0073 Δ rfbP Δ fliC Δ fljB Δ ompA with plasmid pHbp+UreB-VacA This study QS0074 Δ rfbP Δ fliC Δ fljB Δ ompA with plasmid pHbp+UreB- CagA This study QS0075 ΔrfbP ΔfliC ΔfljB Δ ompA with plasmid pHbp+VacA-CagA This study QS0076 Δ rfbP Δ fliC Δ fljB Δ ompA with pHbp+UreB This study QS0077 Δ rfbP Δ fliC Δ fljB Δ ompA with pHbp+VacA This study QS0078 Δ rfbP Δ fliC Δ fljB Δ ompA with pHbp+CagA This study QS0081 Δ rfbP Δ fliC Δ fljB Δ ompC [ 8 ] QS0082 Δ rfbP Δ fliC Δ fljB Δ ompC with plasmid Hbp+UreB-VacA-CagA This study QS0091 Δ rfbP Δ fliC Δ fljB Δ ompD [ 8 ] QS0092 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Typhimurium UK-1 [ 12 ] QS0071 S . Typhimurium UK-1 ∆ rfbP ∆ fliC ∆ fljB ∆ ompA [ 8 ] QS0072 Δ rfbP Δ fliC Δ fljB Δ ompA with plasmid pHbp+UreB-VacA-CagA This study QS0073 Δ rfbP Δ fliC Δ fljB Δ ompA with plasmid pHbp+UreB-VacA This study QS0074 Δ rfbP Δ fliC Δ fljB Δ ompA with plasmid pHbp+UreB- CagA This study QS0075 ΔrfbP ΔfliC ΔfljB Δ ompA with plasmid pHbp+VacA-CagA This study QS0076 Δ rfbP Δ fliC Δ fljB Δ ompA with pHbp+UreB This study QS0077 Δ rfbP Δ fliC Δ fljB Δ ompA with pHbp+VacA This study QS0078 Δ rfbP Δ fliC Δ fljB Δ ompA with pHbp+CagA This study QS0081 Δ rfbP Δ fliC Δ fljB Δ ompC [ 8 ] QS0082 Δ rfbP Δ fliC Δ fljB Δ ompC with plasmid Hbp+UreB-VacA-CagA This study QS0091 Δ rfbP Δ fliC Δ fljB Δ ompD [ 8 ] QS0092 …”
Section: Methodsmentioning
confidence: 99%
“…Native OMVs (without any detergent treatment) were collected and isolated from culture supernatants of S . Typhimurium χ3761 and its mutants as previously described [ 8 , 16 ]. Briefly, 2 L of bacteria culture supernatants in the logarithmic phase (OD 600 = 1) were collected and filtered using a 0.45 μm Steritop bottle-top filter unit (Millipore et al, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it has been shown that disruption of small noncoding RNA improves the protective efficacy of OMVs against Helicobacter pylori infection in a mouse model [ 72 ]. Both intranasal and intraperitoneal immunization with flagellin-deficient S. typhimurium OMVs resulted in efficient protection against heterologous S. choleraesuis and S. enteritidis challenge [ 73 ] and immunization with OMVs from major outer membrane protein-deficient S. typhimurium mutants enhanced cross-protection [ 74 ].…”
Section: Trends Emerging In Preclinical Studiesmentioning
confidence: 99%